Transfiguring Mindanao a Mindanao reader - Canuday, Jose Jowel; Sescon, Jose T. (Quezon City, Philippines Ateneo de Manila University Press, 2022)
This book has 34 chapters with 44 authors mostly coming from Mindanao covering broad topics from history, social, economic, political, and cultural features of the island and its people.--From the publisher.
Population shifts, dislocated peoples: the Mindanao-Sulu story in maps and charts / Rudy Buhay Rodil -- Making of a multicultural city: Zamboanga at the end of Spanish colonialism / Felice Noelle M. Rodriguez -- diversity and divergence: challenges in the formation of the Bangsamoro nation / Juvanni A. Caballero and Manuel Sabdullah R. Tawagon -- The migrants of Mindanao and nation-building: perils, triumphs, and the question of integration / Faina C. Abaya-Ulindang -- Urbanism and settlements in Mindanao: centering the built environment in Mindanao history, culture, and society / Erik Akpedonu and Czarina A. Saloma -- The ghost of Bro Lou and the lost bells: memorializing a forgotten martyr of an unmarked global war / Ma. Christina Agdeppa-Canones -- Islamic formations in Mindanao: diverse traditions, one faith, singular God / Sheik Mahir Gustahan -- Mulitple identifiers, multiple streams: narratives and discourse on Filipino Muslim spirituality -- Indigenized Islamic traditions: the customary law of the Sama Banguinguih in Simariki Island / Yusuf Roque Morales -- The Tausug spirituality: indigenous roots, Islamic Practices / Darwin J. Absari -- Christianity in Mindanao: a brief historical survey / Antonio F.B. de Castro and Amado T. Tumbali Jr. -- The Mindanao church experience: engaging and transforming pastoral ministries in the Philippines / Karl M. Gaspar -- Militant engagements: the Protestant churches in Mindanao socio-political issues / Melanio L. Aoanan -- (Re)Making frontier knowledge: the transformation of Tagakaolo farming in twentieth-century plantation colonialism / Albert J. Santos -- Surviving the frontier: external trade and internal development in American colonial Davao's progress industry / Patricia Irene N. Dacudao -- Marine cultures, coastal economy: national economic contributions of the Mindanao seaweeds and fishing industries in the Zamboanga Peninsula / Teresita A. Narvaez -- Fertile lands, small farms: agrarian patterns and perpetual underdevelopment of Mindanao countrysides / Marjorie S. Muyrong and Ryan Joseph R. Dizon -- Heightened development and persistent distress: the Mindanao political economy / Eduardo C. Tadem -- Neglected economy, arrested progress: Southern impact of a northern-centric development / Joseph Y. Lim, Mildred M. Estanda, Ma. Ritchell D. Abordo, and Diana Carmela G. Taganas -- Deepening impoverishment: human development and socio-economic mobility in Mindanao / Philip Arnold P. Tuano -- Struggling for creation: defending the last of Mindanao watersheds / Reynaldo D. Raluto -- Ecology and society: collective action for the environment / Randy Jasper C. Odchigue -- Shooting Mindanao: how the press reports Mindanao from a photojournalist viewpoint / Robert Timonera -- News viewing as media ritual: broadcast news and national belonging / Estelle Marie M. Ladrido and Ariel Robert Ponce -- Truth-telling in the time of conflict: coverage of the Marawi Siege and beyond / Luz Rimban -- Reporting Martial Law: exposing atrocities and repression through the micro-media reportorial facility / H. Marcos C. Mordeno -- Belonging and otherings: the mobilization and contestation of the Shari'ah in the Bangsamoro Law social media campaigns / Mansoor L. Limba -- Local frontlines of globalized Islamic states networks: the emerging war arena for the Filipino soldier / Gail Tan Ilagan -- Nationalized symbols of injustices: contemporary sources of Bangsamoro grievances / Jamail A. Kamlian and Juvanni A. Caballero -- Tradition or benefits: the Sama-Bajau indigenous and formal education dilemma / Mark francis Francisco -- Bangsamoro and indigenous peoples' history in education: pathways to solidarity and nation-building / Jane Ruby J. Asperin -- Pansak yakan: dancing in time with the past / Earl Francis C. Pasilan -- Vessels of worldview: the Mindanao multicultural experience in the shaping of Filipino martial arts / manolo Luis del Rosario -- Multilingual Mindanao: the future of learning in Pluriverse Mindanao schools / Robin Atilano de los Reyes.
Includes bibliographical references and index.
Keywords: Mindanao -- Economic conditions; Mindanao -- History; Mindanao -- Social life and customs